Relationship between physiological parameters and performance during a half-ironman triathlon in the heat - Del Coso, J.; González, C.; Abian-Vicen, J.; Salinero Martin, J. J.; Soriano, L.; Areces, F.; Ruiz, D.; Gallo, C.; Calleja-Gonzalez, B. L.; Calleja-Gonzalez, J. (Journal of Sports Sciences, 2015)
Triathlon is a popular outdoor endurance sport performed under a variety of environmental conditions. The aim of this study was to assess physiological variables before and after a half-ironman triathlon in the heat and to analyse their relationship with performance. Thirty-four well-trained triathletes completed a half-ironman triathlon in a mean dry temperature of 29 ± 3ºC. Before and within 1 min after the end of the race, body mass, core temperature, maximal jump height and venous blood samples were obtained. Mean race time was 315 ± 40 min, with swimming (11 ± 1%), cycling (49 ± 2%) and running (40 ± 3%) representing different amounts of the total race time. At the end of the competition, body mass changed by -3.8 ± 1.6% and the change in body mass correlated positively with race time (r = 0.64; P < 0.001). Core temperature increased from 37.5 ± 0.6ºC to 38.8 ± 0.7ºC (P < 0.001) and post-race core temperature correlated negatively with race time (r = -0.47; P = 0.007). Race time correlated positively with the decrease in jump height (r = 0.38; P = 0.043), post-race serum creatine kinase (r = 0.55; P = 0.001) and myoglobin concentrations (r = 0.39; P = 0.022). In a half-ironman triathlon in the heat, greater reductions in body mass and higher post-competition core temperatures were present in faster triathletes. In contrast, slower triathletes presented higher levels of muscle damage and decreased muscle performance.